The Emergency Management and Treatment of Severe Burns - Melanie Stander; Lee Alan Wallis (Emergency Medicine International)
Burn injuries continue to cause morbidity and mortality internationally. Despite international collaborations and preventative measures, there are still many cases reported in high- and low-income countries. The treatment of these patients is often protracted and requires extensive resources. The adequate resuscitation of these patients coupled with meticulous wound care can have a huge impact on their outcome. The authors present a simple guideline for the initial management of severe burns which is utilised by the South African Burn Society and is based on the guidelines of the American Burn Association and the Australian and New Zealand Burn Association.